Identification of the significant factors determining extractability of Ni and Cu after sulfation roasting of a PGM-bearing chromitite ore - Mpinga, C.; Eksteen, Jacques; Aldrich, C.; Dyer, Laurence (Elsevier, 2017)
Selective sulfation-roast-water leach process of a complex, chromite-rich Cu-Ni-PGM ore to dissolve water-soluble base metal sulfates contained therein was investigated as an alternative process to remove base metals prior to the extraction of precious metals. Ground run-of-mine ore (P80 < 75 µm) was mixed with concentrated H2SO4 (sulfating agent) and Na2SO4 (dual catalyst and sulfating agent) to intensify atmospheric sulfation roast reaction in an unvented electric furnace (static roast under reducing conditions). The acquired calcine was water leached to extract the Ni and Cu sulfates. The roasting conditions were optimized using a Response Surface Methodology which included a Desirability Function Approach in order to maximize Cu and Ni extraction whilst limiting reagent consumption and suppressing Fe and Cr co-dissolution. It was possible to decompose the chromatic-ferritic structure and produce water-soluble metal species by roasting the ore containing 12.80 g/t Pt, 15.20 g/t Pd, 0.0646% Cu, 0.31% Ni, 13.60% Fe and 10.40% Cr. Approximately 90% Ni and 77% Cu were recovered after roasting at 550 °C in closed atmosphere for 2 h with 462 kg/t H2SO4, 76.9 kg/t Na2SO4 and by leaching at 80 °C with 2 wt% solid density for 24 h. The raw ore, roasted mass and water-leach residue were characterized by fire assay and Tescan Integrated Mineral Analysis (TIMA GM Model). Pt + Pd grade has been upgraded from 28 (raw ore) to 32.38 g/t (water-leach residue).